(untitled) (Research, Society and Development, 2021)
Objective: To define the profile of the gynecological cytopathology exams performed at the Women’s Health Center from October 2018 to October 2019. Methodology: this is a descriptive research with a quantitative approach and of a documentary nature, in which data from registers were used. secondary in the analyzed period, considering the information on the number of changes seen in the tests performed, cases related to the HPV virus, the number of biopsies performed and the age groups of the patients assisted in the chosen months. Results: it was observed that a greater expression of ASC-US changes detected in the registered exams, in addition to HPV detection in almost every month analyzed. Conclusion there is a need to monitor and value the data and information on care services in the area of ​​cytopathology, to avoid underreporting and provide greater control of these data, reinforcing the active search for pathologies related to the cervix, such as cancer.